RESPON MASYARAKAT TERHADAP PELAKSANAAN SIDANG ISBAT KEMENTERIAN AGAMA REPUBLIK INDONESIA DALAM MENETAPKAN RAMADHAN DAN IDUL FITRI: RESPON MASYARAKAT TERHADAP PELAKSANAAN SIDANG ISBAT KEMENTERIAN AGAMA REPUBLIK INDONESIA DALAM MENETAPKAN RAMADHAN DAN IDUL FITRI - Nursyamsyah, Idham; Anis, Muhammad (HISABUNA: Jurnal Ilmu Falak, 2025)
ABSTRACT This article discusses the perceptions of the people of Barombong District, Gowa Regency regarding the implementation of isbat meetings by the Ministry of Religion of the Republic of Indonesia, this paper examines in depth how the results of isbat meetings are in the public's view. This research is classified as field research with a syar'i and sociological approach, the data used comes from interviews and field observations. The results of research on people's perceptions of the people of Barombong Sub-District regarding the implementation of isbat meetings, the community considers that isbat meetings are very important to provide certainty to the community besides that the community thinks that the decisions of isbat meetings are government policies that are part of the duties and functions of the Ministry of Religion as a government representation. The response of the Barombong Subdistrict Community to the decision of the Isbat meeting in determining the beginning of the month of Ramadan and Eid al-Fitr, the majority of the people make the decision of the Isbat meeting as a reference or guide in carrying out Ramadan and Eid al-Fitr fasting, this certainly strengthens the position and role of the Ministry of Religion as the government's representative in deciding and establishing implementation of Ramadan and Eid al-Fitr fasting in Indonesia. It is hoped that the Ministry of Religion will make efforts to approach Islamic organizations in Indonesia to create a new formula in the framework of unifying Islamic holidays in Indonesia. It is hoped that experts, experts, academics and practitioners of astronomy will study and explore the method of determining the beginning of the lunar month by seeking the presence of standardization methods nationally as well as efforts to unify the international Islamic calendar.